Novel Echocardiography-Derived Left Ventricular Stiffness Index in Low-Flow Versus Normal-Flow Severe Aortic Stenosis with Preserved Left Ventricular Ejection Fraction - Ngiam, Jinghao Nicholas (Sci Rep, 2020)
Background Paradoxical low-flow (LF) severe aortic stenosis (AS) with preserved left ventricular ejection fraction (LVEF) may have poorer prognosis than normal-flow (NF) AS, though its pathophysiology remained unclear. In particular, LV stiffness has not been compared between LF vs NF. We used a novel echocardiography-derived index of LV stiffness to compare between these groups. Consecutive patients with medically-managed isolated severe AS (aortic valve area < 1 cm(2)) and preserved LVEF (>50%) were studied. Echocardiographic LV stiffness index was measured by a method previously validated against cardiac catheterization. We compared LF (stroke volume index, SVI < 35 ml/m(2)) and NF severe AS. Of the 352 patients, 121 (34%) were LF. Both LF and NF groups had similar demographics, valve areas and indices. Compared to NF, LF severe AS had higher LV stiffness indices (>0.11 ml(−1) OR 3.067, 95% CI 1.825–5.128, p < 0.001). Increased LV stiffness was associated with concentric remodelling and more severe diastolic dysfunction, especially in LF AS. An LV stiffness index of > 0.11 ml(−1) was independently associated with increased mortality, after adjusting for age, clinical and echocardiographic parameters (HR 2.283 95% CI 1.318–3.968, p = 0.003). Non-invasive echocardiographic-derived index of LV stiffness may be important in LF AS. Increased LV stiffness was related to LV concentric remodelling and diastolic dysfunction, and associated with poorer clinical outcomes in medically-managed AS.